Until Sniffer Dogs Can Talk: CRIM-TRACK - Hardy, Iona (Cranfield University, 2022)
This image is a digitally drawn short comic highlighting the CRIM-TRACK sniffer, a device that utilises a colourimetric sensor system to detect illicit compounds by their vapour at sensitivity rivalling a sniffer dog, but with better discrimination. Both detection methods can detect multiple substances, but sniffer dogs cannot signal which substance they have found, whilst the CRIM-TRACK sniffer can. The research aims to contribute to developing the CRIM-TRACK sniffer device, specifically the disposable colourimetric microchips used. This is being carried out by investigating the colour change mechanisms of select dyes when they encounter illicit compounds such as illicit drugs, homemade explosives, and their precursor chemicals using common analytical techniques. This data will allow future generations of the microchip to be tuned via dye selection for specific scenarios.
Keywords: CRIM-TRACK; Colourimetric detection; Illicit drugs; DSDS2022; DSDS2022 Digital Image